Trends in Adjuvant Therapy After Surgery for Oropharyngeal Squamous Cell Carcinoma. (23rd September 2021) - Philips, Ramez; Sagheer, Hamad; Barsouk, Adam; Swendseid, Brian; Johnson, Jennifer; Bar Ad, Voichita; Luginbuhl, Adam; Curry, Joseph; Cognetti, David
Abstract : Objectives/Hypothesis: We aim to 1) evaluate trends in adjuvant treatment of human papilloma virus (HPV)‐related oropharyngeal cancer; 2) assess change in complications and functional outcomes over time; and 3) assess change in overall and disease‐free survival (DFS) over time. Study Design: Retrospective analysis. Methods: Charts of patients who underwent transoral robotic surgery for HPV‐related oropharyngeal cancer between 2011 and 2019 were reviewed. Trend analysis was used to compare rate of adjuvant treatment over time. The Kaplan–Meier method was conducted to analyze overall survival (OS) and DFS. Results: Three hundred and forty‐two patients met inclusion criteria. One hundred and sixty‐three (47.7%) patients underwent adjuvant radiation, and 90 (26.3%) patients underwent adjuvant chemoradiation. Rate of extranodular extension decreased significantly from 38.9% to 24.0% ( P =  .004). Rate of adjuvant therapy decreased significantly from 90.9% to 62.5% between 2011 and 2019 ( P  = .001). In patients who received adjuvant treatment, rate of adjuvant chemoradiation therapy decreased significantly from 40.0% to 20.0% ( P  < .0005). There was a decrease in rate of 1‐year gastrostomy tube dependence in patients treated in 2015 to 2019 versus 2011 to 2014 (2.2% vs. 7.1%, P  = .025). In 2011 to 2014, 2‐year OS and DFS were 96% and 89%, respectively; in 2015 to 2019, 2‐year OS and DFS were 96% and 94%, respectively. There was no difference in OS or DFS between the two time periods. Conclusions: The rate of adjuvant therapy, particularly chemotherapy, has decreased over time. One‐year gastrostomy tube dependence rate has decreased significantly from 2011 to 2014 to 2015 to 2019. There was no change in OS and DFS over this time period. Level of Evidence: 3 Laryngoscope, 132:806–812, 2022